Ethics of Intelligent Vehicles Technology: A Comprehensive Review - Karpurapu, Sailatha; Raghuram J, Naga Venkata (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Intelligent vehicles technology is growing with new developments and mobility systems. These developments arise so many implications in an ethical manner. Specifically in some scenarios i.e., vehicle uncontrolled situations by automation systems, program failure conditions in driving time, and many more. In this situation, who is responsible? The literature section explored the existing studies of who, how and when designed the ethics. The policy makers and standard organizations are designed some policies and recommended to the government which present following the policy system. These policies are only concerned about public health, environmental issues, road safety, traffic congestion and many more. But in few areas found implications i.e., data privacy, cyber security, cost and decision-making system etc. by existing studies. To improve this autonomous technology public fully acceptance is must. For the adoption of this technology, users get more benefits such as travel time, safety, mobility, no traffic, less environment issues etc. and at the same time some factors also influencing. Ethical and policy systems are linked to acceptance of this technology. Above ethics, policy and public acceptance of these technology areas are investigated and found to have some implication gaps. This paper aims to present the existing studies and implications in ethics, policy and public acceptance of this technology area. In future, this review study will recommend to all those doing research, engineers, philosophers, policy design government sections to develop the sustainability system in intelligent vehicles.